Sports injuries and prevention (Springer Japan, 2015)
This book presents the incidence of sports-related injuries, the types of injuries specific to particular sports, and the importance of factors such as age and gender. Possible injury mechanisms and risk factors are presented based on an analysis involving recent scientific findings. A variety of sports are included to allow the reader to better generalize the results as well as to apply appropriate procedures to specific sports. The authors have emphasized basic scientific findings to help the reader gain a broad knowledge of sports injuries. The potential audience includes medical doctors, physical therapists, athletic trainers, coaches and interested parents. This book is expected to play a prominent role in the construction of training programs for both healthy and injured players. The focus on junior athletes will aid in their education, injury prevention and increased performance. It will also benefit instructors at the junior and senior high school levels.